Diastematomyelia and spinal teratoma in an adult. Case report. - (:unkn) unknown (My University, 2001)
Diastematomyelia, or split cord malformation, a complete or incomplete sagittal division of the neural axis into halves, is seen in association with many other congenital anomalies. Among these anomalies, intradural spinal teratoma is extremely rare. Diastematomyelia is a well-recognized although unusual clinical syndrome in children, but it is rarely reported in the adult. The authors describe a 42-year-old man who presented with pain and distal left-leg weakness as well as neurogenic claudication for 1 month. The patient underwent radiological examinations, and diastematomyelia and an intradural lumbar teratoma were diagnosed. He underwent surgery and was followed for 1 year. This is the fourth case of an adult who simultaneously presented with diastematomyelia and an intradural teratoma.